Penggunaan Abu Kulit Kerang Sebagai Bahan Pengisi (Filler) Dalam Campuran Aspal Jenis Ac-Wc Dengan Pengujian Marshall - Fandy Agisman; Alfian Malik; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In asphalt concrete mixture. Filler has the smallest percentage composition compared to coarse and fine aggregates. Portland cement, lime stone ash and fly ash are commonly used as filler but they are relatively expensive. Therefore, it is composition to find alternative cheap materials. Clam shell ash is one of those materials that can be found relatively cheaper. The aim of this research is to examine the performance of clamshell ash filler in Asphalt Concrete Wearing Course (AC-WC) mixture that comply with Bina Marga 2010 revision 3 spesification. The type of asphalt used in this research is Pen 60/70. In the determination of KAO, the approximate variations of optimum asphalt content were 5%, 5.5%, 6%, 6.5% and 7%. Clamshell ash proportion used 0%, 2%, 4%, 6% and 8%.The results of this study showed that the performance of AC-WC mixture using shell ash filler has better stability value than without it. Recommended shell ash filler content for AC-WC mixture that comply with the spesification is 4%.Keywords: shell ash, General Specification of Bina Marga 2010, filler, Marshall, AC-WC